Successful Management of Arthrogryposis and Brachygnathic Buffalo Calf Through Pervaginal Delivery- A Case Report - Deepak; Hanuman Prasad Yadav; Umed Singh (The Indian Veterinary Journal, 2024)
A case of dystocia associated with malpresentation and a typical monster with arthrogryposis brachygnathia and kyphosis was delivered through per-vaginal manual traction with mutation in a fully dilated cervix of Murrah buffalo.